Three essays in health and labor economics - Walia, Bhavneet (Kansas State University, 2008)
The dissertation examines empirical issues related to health and labor economics. It has long been debated whether breastfeeding leads to a higher intelligence quotient (IQ) and greater scholastic achievement. The first study empirically examines the issue. Many past studies fail to take into account the possible endogeneity of the breastfeeding decision and thus falsely identify the correlation between breastfeeding and IQ as a causal relationship. We attempt to distinguish the causation and correlation between the two variables. Our results show that, after controlling for possible endogeneity, breastfeeding has no significant impact on IQ or scholastic achievement. The second essay examines the link between breastfeeding and childhood obesity. Heath economics researchers view breastfeeding as a determining factor as to whether a child becomes obese. There are many theories, involving both biological and psychological factors, as to why breastfeeding is negatively linked to childhood obesity. This essay argues that the breastfeeding decision is not an exogenous one, so estimation technique such as ordinary least squares is not the correct way to estimate the relationship between breastfeeding and childhood obesity. Instruments are used to generate exogenous variations in the breastfeeding variable. After correcting for any estimation bias due to the breastfeeding variable being endogenous, this study documents the benefits of breastfeeding. The third essay analyzes 19 semesters of student evaluations at Kansas State University. Faculty fixed effects are sizable and indicate that, as assessed by students, the best principles teachers also tend to be the best non-principles teachers. OLS estimates are biased because principles teachers are drawn from the top of the distribution and because unmeasured faculty characteristics are correlated with such variables as the response rate and student effort. Student ratings are lowest for new faculty but stabilize quickly. Expected GPA of the class is not an important determinant of student ratings, but equitable grading is; and the rewards for equitable grading appear larger for principles classes. The lower ratings in principles classes are fully accounted for by greater class size.
Keywords: Health economics; Labor economics; Teaching economics; Education; Economics, General (0501); Education, Health (0680)